The curriculum development team's role in facilitating technology learning at SD Budiluhur - Najwa Nabila Hermawan (Himpunan Pengembang Kurikulum Indonesia, 2025)
The digital transformation in education requires elementary schools to equip students with technological skills from an early age. Adaptive and integrative curricula, such as the Kurikulum Merdeka, offer significant opportunities to develop digital literacy through contextual and project-based learning. However, challenges such as limited facilities and insufficient teacher training remain obstacles to implementing ICT-based learning. This study aims to describe the role of the curriculum development team in shaping students’ technology competence at SD Budiluhur. A descriptive qualitative approach was employed, using interviews and observations involving teachers, the principal, and members of the curriculum development team. The findings indicate that the team actively contributes to the design of technology-integrated teaching materials, the selection of appropriate digital tools, and the provision of ongoing teacher training. The curriculum implemented at SD Budiluhur has enhanced students' interest and ability to use technology wisely and productively. This study highlights the importance of collaboration and innovative curriculum strategies in creating a learning environment that is responsive to technological advancements. Abstrak Transformasi digital dalam dunia pendidikan menuntut sekolah dasar untuk membekali murid dengan keterampilan teknologi sejak dini. Kurikulum yang adaptif dan integratif, seperti Kurikulum Merdeka, memberikan peluang besar untuk mengembangkan literasi digital melalui pembelajaran yang kontekstual dan berbasis proyek. Namun, tantangan seperti keterbatasan fasilitas dan kurangnya pelatihan guru masih menjadi hambatan dalam implementasi pembelajaran berbasis TIK. Penelitian ini bertujuan untuk menggambarkan peran Tim Pengembang Kurikulum (TPK) dalam membentuk kompetensi teknologi murid di SD Budiluhur. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode wawancara dan observasi terhadap guru, kepala sekolah, dan anggota TPK. Temuan menunjukkan bahwa TPK berperan aktif dalam merancang materi ajar berbasis teknologi, memilih perangkat digital yang sesuai, serta memberikan pelatihan berkelanjutan kepada guru. Kurikulum yang diterapkan di SD Budiluhur mampu meningkatkan minat dan kemampuan murid dalam menggunakan teknologi secara bijak dan produktif. Penelitian ini menegaskan pentingnya kolaborasi dan strategi kurikulum yang inovatif untuk menciptakan lingkungan belajar yang responsif terhadap perkembangan teknologi. Kata Kunci: kompetensi teknologi; kurikulum merdeka; pengembangan kurikulum; sekolah dasar